Longitudinal “Real-World” Outcomes of Pirfenidone in Idiopathic Pulmonary Fibrosis in Greece - Tzouvelekis, Argyrios; Karampitsakos, Theodoros; Ntolios, Paschalis; Tzilas, Vasilios; Bouros, Evangelos; Markozannes, Evangelos; Malliou, Ioanna; Anagnostopoulos, Aris; Granitsas, Andreas; Steiropoulos, Paschalis; Dimakou, Katerina; Chrysikos, Serafeim; et al. (Frontiers in Medicine, 2017)
Background: Pirfenidone is an antifibrotic compound able to slow down disease progression in patients with idiopathic pulmonary fibrosis (IPF). Objective: To investigate the safety and efficacy of pirfenidone in patients with IPF in a real-life setting. Methods: This was a multi-center, retrospective, real-life, observational study for patients with IPF receiving pirfenidone. Results: We identified 92 patients with IPF receiving pirfenidone. Eighty patients (70 males, 10 females, mean age±SD: 68.1+7.5, mean%FVC±SD=74.9+17.2, mean%DLCo±SD=48.1+16.9) were included in the analysis. Skin-related (25%) and gastrointestinal (17.5%) adverse events were the most common and led to drug discontinuation in 22.5% of cases. The majority (87%) of patients experienced side-effects during the first 6 months of treatment. At 36 months, changes in %FVC and % DLCO were -9.25±16.34 and -9.26±15.26, respectively. Six, 12 and 24 months after treatment initiation (n=80, 60, and 26), 18, 15 and 5 patients (22.5, 25 and 19.2%) experienced significant (>10%) and 11, 3 and 3 (13.8, 5 and 11.5%) marginal (5 to 10%) %FVC improvement. Thirteen, 6 and 1 (16.2, 10 and 3.9%) experienced marginal (-5 to -10%) and 20, 21 and 8 (25, 35, and 30.8 %) significant decline (<-10%) in %FVCpred, at 6, 12 and 24 months after treatment initiation, respectively. Median survival was 851 days and 41 patients died during the study period. Conclusion: Pirfenidone demonstrated an acceptable safety and therapeutic profile in patients with IPF on a longitudinal basis. Prospective observational registries are sorely needed to provide a real-world view of pirfenidone outcomes in clinical practice.